2021
DOI: 10.1016/j.xjon.2021.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Short-term outcomes of aortic valve neocuspidization for various aortic valve diseases

Abstract: Objectives: Bioprosthetic valve deterioration remains a major limitation following aortic valve replacement. Favorable results have been reported with an autologous pericardium aortic valve neocuspidization.Methods: Seventy patients (31 women and 39 men) (mean age, 62 AE 12 years) with aortic stenosis (n ¼ 52 [74%]) or aortic regurgitation (n ¼ 18 [26%]) underwent the aortic valve neocuspidization procedure. Thirty-four patients (49%) had a tricuspid valve, 35 (50%) had a bicuspid valve, and 1 (1%) had a monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Also, Nguyn et al (6) in 2018 published a study including nine patients who underwent a minimally invasive Ozaki procedure. The authors reported a shorter ventilation time (8.4 hours), a shorter time at the ICU (1.6 days) and a shorter hospitalization time (5.8 days) in comparison with other studies (9) .…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Also, Nguyn et al (6) in 2018 published a study including nine patients who underwent a minimally invasive Ozaki procedure. The authors reported a shorter ventilation time (8.4 hours), a shorter time at the ICU (1.6 days) and a shorter hospitalization time (5.8 days) in comparison with other studies (9) .…”
Section: Discussionmentioning
confidence: 40%
“…The average age was 54 ± 16.4 years (range, 13.8-78.5). 436 individuals who had AVR were investigated by Khatchatourov et al (9) with a mean age of 62.11 years, they included 70 patients (31 women and 39 men) who had autologus intervention. 18 patients (26%) had AR, 7 patients (10%) had both AS and AR, and 45 patients (64%) had AS.…”
Section: Discussionmentioning
confidence: 99%
“…It is inevitable that the duration of cross-clamping will be longer. [ 12 ] After the operation, serious decreases are provided in aortic valve gradient with values similar to native valve. A meta-analysis in 2023 for 1891 patients that underwent AV-Neo using the Ozaki technique provided that mean peak gradient was 15.7 mm Hg in aortic valve and had only %0.25 aortic valve insufficiency after operation.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of JTCVS Open , Khatchatourov and colleagues 1 present an impressive series of 70 patients who underwent aortic valve replacement via reconstruction of a new valve with native or xenograft pericardial tissue. This technique, first described by Ozaki and colleagues in 2011, offers an alternative to conventional valve replacement.…”
mentioning
confidence: 99%